Development of a discrimination network for conducted EMI analysis - Ohnmar Tun. (2008)
This thesis aims to develop and design a CM/DM discrimination network that allows separate measurements of CM and DM conducted emissions from the SMPS. Three possible discrimination networks are identified and their performances are evaluated. Finally, the discrimination network with the best performance is chosen for CM/DM noise discrimination purpose. Finally, the application aspect of the discrimination network is also demonstrated through a practical power line filter design example.